1997
DOI: 10.1037/1040-3590.9.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Do partners agree about abuse in their relationship?: A psychometric evaluation of interpartner agreement.

Abstract: This study tested whether partners can be relied on to provide congruent reports about abuse in their relationship. The authors examined whether interpartner agreement (IA) varies as a function of whether the perpetrator is the man or the woman, and by whether the abusive behavior being reported is physical or psychological. Guided by psychometric test theory, the authors examined whether weak IA about specific behaviors can be improved by aggregating behavior items into scales and by controlling for random me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
295
3
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 302 publications
(313 citation statements)
references
References 49 publications
14
295
3
1
Order By: Relevance
“…Even if this finding agrees with several previous reports 16,17,18,22,23,28,34,35,36 , it has the strength of being based on a full information factor analysis. Note that this result is central to what follows, since a single dimensionality of a scale being scrutinized is essential to render item response theory interpretable 24 .…”
Section: Discussioncontrasting
confidence: 36%
“…Even if this finding agrees with several previous reports 16,17,18,22,23,28,34,35,36 , it has the strength of being based on a full information factor analysis. Note that this result is central to what follows, since a single dimensionality of a scale being scrutinized is essential to render item response theory interpretable 24 .…”
Section: Discussioncontrasting
confidence: 36%
“…A methodological study demonstrated strong reliability and validity for the partner violence scale (i.e., 0.89 internal consistency and 75% inter-partner agreement). 37 Children in the 'probable' maltreatment category were classified as having physical abuse exposure if their families were in the top 5% of the distribution of partner violence at either the age-5 or age-7 assessments. This method resulted in 28 boys from the 'probable maltreatment' group being added to the group of children we classified for this article as having been exposed to physical abuse.…”
Section: Physical Abuse Exposurementioning
confidence: 99%
“…Potential items were selected by reviewing existing measures of delinquency (which included items relating to general violence and non-violent offending) and partner violence and, in order to include a broad range of both violent and non-violent criminal acts (e.g., Bendixen & Olweus, 1999;Borjesson, Aarons, & Dunn, 2003;Dahlberg, Toal & Behrens, 1998;Huizinga, Esbensen, & Weiher, 1991;Mak, 1993;Moffitt & Silva, 1988;Moffitt et al, 1997;Straus, 1979;Straus, Hamby, Boney-McCoy, & Sugarman, 1996). Initially, 119 items were selected from the literature review and a pilot study was conducted to investigate the prevalence of the behaviors in women as violent and criminal scales tend to be developed on men.…”
Section: Methods Item Selectionmentioning
confidence: 99%